Reaction to Deceptive Advertising in Brazil - D, Kamlot; D, Botelho; FB, Oliveira (International Journal of Advances in Management and Economics, 2018)
This paper examines the Brazilian consumers and their reaction to deceptive and non-deceptive advertisings. Two versions of the same ad – one without and another with deception – were exposed to 359 respondents and reactions compared using the Wells scale. It was found that consumers tend not to claim their rights in court when faced by deceptive advertisement. Also, the emotional quotient (EQ) of the deceptive advertisement exceeds that of the non-deceptive, indicating that consumers perceive greater appeal in a deceptive advertisement than in the non-deceptive. The deceptive advertisement is even perceived as more honest than the non-deceptive. Keywords: Deceptive Advertising, Reaction. Brazil, Consumers.